Sam and Sam Clark: Moro. The Cookbook - Davidson, Alan E (Petits Propos Culinaires, 2024)
Sam and Sam Clark: Moro. The Cookbook: Ebury Press, 2001: ISBN 0-09-187483-1, 288 pp., many photographs, h/b, £25.00.